Integrated studio & systemic architectural design: architecture, landscape and social inclusion - Tardin-Coelho, Raquel; Racca, Gustavo (Rio Books, 2023)
This publication addresses the above topics and presents Integrated Studios as opportunities to develop sustainable systemic architectural designs. It specifically focuses on the practical experience of Integrated Studio 1, developed at the Faculty of Architecture and Urban Planning of the Federal University of Rio de Janeiro, Brazil. This case study serves as a concrete example of how these studios can meet the demands of constantly changing urban realities.